Classification and characteristics of soil arching structures in pile-supported embankments. (June 2018) - Lai, Han-Jiang; Zheng, Jun-Jie; Zhang, Rong-Jun; Cui, Ming-Juan
Abstract: Soil arching effect is a key load-transfer component in pile-supported embankments. However, previous models that account for soil arching effect consider various assumptions and simplifications due to insufficient understanding of soil arching structures developed in pile-supported embankments. Consequently, the use of previous models in practice would potentially result in substantially different designs. This study aims to develop a reasonable classification system for the soil arching structures under different conditions, and to identify the characteristics and applicability of each structure. Firstly, a series of Discrete Element Method simulations were performed to investigate the evolution of soil arching structures under different conditions with emphasis on the embankment deformation behaviour. The simulation results show that soil arching structures under different conditions can be divided into three groups: (a) "shear plane arching"; (b) "partial arching"; and (c) "full arching". This was followed by detailed analysis of the macro- and microscopic characteristics of each soil arching structure. Finally, the load-transfer mechanisms of the three soil arching structures are compared, and the influence of design parameters on the soil arching structure is discussed. It is concluded that contact force rotation induced by the pile-subsoil relative displacement causes the changes in load-transfer path, and thus the stress distribution is altered. However, the interaction and location of the rotated contact forces are considerably different under different conditions, which results in the development of various soil arching structures and significant differences in the deformation and the load-transfer mechanism of the pile-supported embankments. Two critical heights that govern the interaction and location of the rotated contact forces were identified: the critical arching height, h ca (i.e., 0.8( s - a )), and the critical overlying filling height, h co (i.e., 3.0 a ), where s is the pile spacing and a is the pile (or pile cap) width. It was shown that, for the design of the pile-supported embankments, both ( s - a ) and a should be considered.